PRELIMINARY REPORT ON THE INITIAL GROWTH OF Calycophyllum spruceanum Benth. FROM BROADCAST SEEDS SOWING METHOD - DÍAZ-SORIA, Rossana (2021)
We present the preliminary results of the initial growth of capirona Calycophyllum spruceanum from a broadcast seed sowing in which the seeds were first mixed together with white sand and manually spread over an area of ​​40m2. After germination, biometric measurements were recorded every three months for selected individuals. In 18 months of evaluation, an average height of 3.75m (±0.65) and stem diameter of 3.44cm (±1.46) were reached. This experiment sought to verify the efficacy of the broadcast seed sowing for capirona, a highly valuable timber forest species, which today is at risk of disappearance due to the fact that its natural populations are being affected by overexploitation. The growth figures obtained were satisfactory, which shows that this sowing method is viable in becoming a new propagation alternative for the species.